Química bioortogonal: cuando los organismos vivos se convierten en matraces de reacción - Idiago-López, Javier (2023)
In this article, we introduce the concepts of click chemistry and bioorthogonal chemistry, which have received the Nobel Prize in Chemistry 2022 for their numerous advantages (simplicity, robustness, practically quantitative yields, etc.). We describe the main bioorthogonal reactions that can be carried out in living systems, such as cells and even animals, which become exotic "reaction flasks". We also provide an overview of the latest advances in bionanomedicine, which were made possible by the combination of bioorthogonal chemistry with the unique properties of nanomaterials. To this end, the main characteristics of nanomaterials are presented, and some recent studies related to the development of new imaging and therapeutic tools are described.